The molecular and metabolic landscape of ferroptosis in respiratory diseases: Pharmacological aspects - Tong Wu; Miaorong Ji; Tian Li; Lianxiang Luo (Journal of Pharmaceutical Analysis, 2025)
Ferroptosis is a form of cell death that occurs when there is an excess of reactive oxygen species (ROS), lipid peroxidation, and iron accumulation. The precise regulation of metabolic pathways, including iron, lipid, and amino acid metabolism, is crucial for cell survival. This type of cell death, which is associated with oxidative stress, is controlled by a complex network of signaling molecules and pathways. It is also implicated in various respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), acute lung injury (ALI), lung cancer, pulmonary fibrosis (PF), and the coronavirus disease 2019 (COVID-19). To combat drug resistance, it is important to identify appropriate biological markers and treatment targets, as well as intervene in respiratory disorders to either induce or prevent ferroptosis. The focus is on the role of ferroptosis in the development of respiratory diseases and the potential of targeting ferroptosis for prevention and treatment. The review also explores the interaction between immune cell ferroptosis and inflammatory mediators in respiratory diseases, aiming to provide more effective strategies for managing cellular ferroptosis and respiratory disorders.